Plastic Packaging Waste Management by L’Oreal and Unilever: A Circular Economy Perspective - Rizkovic, Ameral (Journal of World Trade Studies, 2022)
The discussion on environmental conservation cannot be separated from the discussion about plastic waste, which has contributed to environmental disaster. The Circular Economy (CE) concept is a new breakthrough in the discussion of environmental conservation that bridges the gap between the economy and the environment. Through the lens of CE, companies have the responsibility to handle plastic packaging waste. This study seeks to observe the strategies made by the beauty industry companies (L'Oréal and Unilever) in managing plastic packaging waste from CE perspectives and the collaboration between companies, the government, and the community as three important actors in encouraging the implementation of CE in Indonesia. This topic will be analyzed from CE perspectives through a literature review sourced from books, journal articles, company annual reports, company profiles, environmental NGO reports, online articles, and various other sources. This research found that the beauty industry companies (L'Oréal and Unilever) have various programs and strategies to implement CE through handling plastic packaging waste. However, the implementation of these programs has minimal adoption of CE principles. In addition, to implement CE in Indonesia, it is necessary to improve the interaction between the three actors. The Triple Helix model becomes a reference for the interaction model between the three actors which emphasizes circulation from one institution to another to encourage dialogue and better understanding.